A Bayesian hierarchical approach to quantifying stakeholder attitudes toward conservation in the presence of reporting error. Issue 2 (17th December 2019) - Vasudev, Divya; Goswami, Varun R.
Abstract: Stakeholder support is vital for achieving conservation success, yet there are few reliable mechanisms to monitor stakeholder attitudes toward conservation. Approaches used to assess attitudes rarely account for bias arising from reporting error, which can lead to falsely reporting a positive attitude toward conservation (false‐positive error) or not reporting a positive attitude when the respondent has a positive attitude toward conservation (false‐negative error). Borrowing from developments in applied conservation science, we used a Bayesian hierarchical model to quantify stakeholder attitudes as the probability of having a positive attitude toward wildlife notionally (or in abstract terms) and at localized scales while accounting for reporting error. We compared estimates from our model, Likert scores, and naïve estimates (i.e., proportion of respondents reporting a positive attitude in at least 1 question that was only susceptible to false‐negative error) with true stakeholder attitudes through simulations. We then applied the model in a survey of tea estate staff on their attitudes toward Asian elephants ( Elephas maximus ) in the Kaziranga–Karbi Anglong landscape of northeast India. In simulations, Bayesian model estimates of stakeholder attitudes toward wildlife were less biased than naïve estimates or Likert scores. After accounting for reporting errors, we estimated the probability of having a positive attitude toward elephants notionally as 0.85 in the Kaziranga landscape, whereas the proportion of respondents who had positive attitudes toward elephants at a localized scale was 0.50. In comparison, without accounting for reporting errors, naïve estimates of proportions of respondents with positive attitudes toward elephants were 0.69 and 0.23 notionally and at local scales, respectively. False (positive and negative) reporting probabilities were consistently not 0 (0.22–0.68). Regular and reliable assessment of stakeholder attitudes–combined with inference on drivers of positive attitudes–can help assess the success of initiatives aimed at facilitating human behavioral change and inform conservation decision making. Abstract : Article impact statement : Misreporting can be a significant source of bias when assessing stakeholder attitudes, but can be accounted for with hierarchical models. Abstract : Una Estrategia de Jerarquía Bayesiana para Cuantificar las Actitudes de Grupos de Interés hacia la Conservación en Presencia de Errores de Información Resumen: El apoyo de los grupos de interés es vital para alcanzar el éxito en la conservación, sin embargo, existen pocos mecanismos confiables para monitorear la actitud de los grupos de interés hacia la conservación. Las estrategias que se usan para valorar las actitudes de los grupos de interés pocas veces toman en cuenta el sesgo que surge de errores en la información, lo cual puede resultar en un falso reporte de actitudes positivas hacia la conservación (error falso positivo) o en que no se reporte una actitud positiva cuando el respondiente tiene una actitud positiva hacia la conservación (error falso negativo). Usamos un modelo de jerarquía bayesiana, construido a partir del desarrollo aplicado en la ciencia de la conservación, para cuantificar las actitudes de los grupos de interés como la probabilidad de tener, teóricamente (o en términos abstractos) y a escalas locales, una actitud positiva hacia la vida silvestre mientras se compensa el error de información. Comparamos mediante simulaciones las estimaciones de nuestro modelo, los puntajes de Likert y las estimaciones ingenuas (es decir, la proporción de los respondientes que reportaron una actitud positiva en al menos una pregunta que se encontraba solamente susceptible al error falso negativo) con las verdaderas actitudes de los grupos de interés. Después aplicamos el modelo al censo realizado al personal de una finca de té sobre sus actitudes hacia los elefantes asiáticos ( Elephas maximus ) en el paisaje de Kaziranga‐Karbi Anglong al noreste de la India. En las simulaciones, las estimaciones de las actitudes de los grupos de interés hacia la vida silvestre generados por el modelo bayesiano estuvieron menos sesgados que las estimaciones ingenuas o los puntajes de Likert. Después de considerar los errores de información, estimamos una probabilidad de 0.85 de que los respondientes teóricamente tuvieran una actitud positiva ante los elefantes en el paisaje de Kaziranga, mientras que la proporción de respondientes con actitudes positivas hacia los elefantes a escalas locales fue de 0.50. Como contraste, sin considerar los errores de información, las estimaciones ingenuas de la proporción de los respondientes con actitud positiva hacia los elefantes fueron de 0.69 y 0.23 teóricamente y a escalas locales, respectivamente. El reporte de falsos (positivos y negativos) en las probabilidades constantemente no fue 0 (0.22 – 0.68). La valoración regular y confiable de las actitudes de los grupos de interés – combinada con la inferencia sobre los conductores de estas actitudes positivas – puede ayudar a evaluar el éxito de las iniciativas enfocadas en facilitar cambios en el comportamiento humano y en informar a las decisiones de conservación.